Avaliação do potencial anti-inflamatório de composto tipo heparina (cCTH) extraído do caranguejo Goniopsis cruentata em modelo experimental de peritonite - Azevedo, Fernanda Marques de (2013)
Heparin, a sulfated polysaccharide, was the first compound used as an anticoagulant and antithrombotic agent. Due to their structural characteristics, also has great potential anti-inflammatory, though such use is limited in inflammation because of their marked effects on coagulation. The occurrence of heparin-like compounds that exhibit anticoagulant activity decreased in aquatic invertebrates, such as crab Goniopsis cruentata, sparked interest for the study of such compounds as anti-inflammatory drugs. Therefore, the objective of this study was to evaluate the potential modulator of heparin-like compound extracted from Goniopsis cruentata in inflammatory events, coagulation, and to evaluate some aspects of its structure. The heparin-type compound had a high degree of N-sulphation in its structure, being able to reduce leukocyte migration into the peritoneal cavity at lower doses compared to heparin and diclofenac sodium (anti-inflammatory commercial). Furthermore, it was also able to inhibit the production of nitric oxide and tumor necrosis factor alpha by activated macrophages, inhibited the activation of the enzyme neutrophil elastase in low concentrations and showed a lower anticoagulant effect in high doses as compared to porcine mucosal heparin. Because of these observations, the compound extracted from crab Goniopsis cruentata can be used as a structural model for future anti-inflammatory agents